Polymorphic locus RS11568818 of the MMP7 gene is associated with the development of essеntial hypertension in women - M. I. Moskalenko; I. V. Ponomarenko; A. V. Polonikov; M. I. Churnosov (Российский кардиологический журнал)
Aim. To study the involvement of polymorphic loci rs1799750 MMR1, rs3025058 MMR3, rs 11568818 MMR7, rs1320632 MMR8 and rs11225395 MMR8 in the development of arterial hypertension (AH) in women of the Central Chernozemny Region of Russia.Material and methods. During the study 584 women were examined: 375 patients with AH and 209 control subjects. Analysis of metalloproteinases’ polymorphic loci was performed using real-time PCR (TagMan probes). Statistical processing of the results was performed using the STATISTICA for Windows 10.0. The regulatory potential of polymorphic loci was analyzed using the HaploReg software (v4.1). Assessment of the effects of single nucleotide polymorphisms on gene expression (cis-eQTL) was performed according to the Genotype-Tissue Expression (GTEx) project.Results. We established that the polymorphic allele G (OR=1,49, 95% CI=1,16-1,92, p=0,002) and the GG genotype (OR=1,64, 95% CI=1,12-2,40, p=0,010) in the rs11568818 locus of MMP7 gene is associated with a high risk of AH in women. Polymorphic marker rs11568818 MMP7 has significant epigenetic effects: located in the region of histones, labeling promoters and enhancers, in the region of binding sites with transcription factors Foxa known1, PLZF, Pou5f1 known2 and GR known4, in binding niche of regulatory proteins TBP, c-FOS, c-Jun. It was found that the polymorphic variant G rs1 1568818 of MMP7 is associated with a reduced level of expression of the MMP7 gene.Conclusion. The polymorphic locus rs11568818 of the MMP7 gene is involved in the development of AH in women of the Central Chernozemny Region of Russia.